Writing letters in Song China (960-1279): a study of its political, social, and cultural uses - Tsui, L (2015)
Even though there has been no lack of scholarly attention to Chinese epistolary texts as a source of information, discussions of the functions and practices of letter writing in imperial China are very limited. This thesis deals with how elites in Song dynasty (960–1279) China exchanged personal and political information by writing and sending letters to each other, and how the genre of letters functioned in its various forms throughout the socially transformative and culturally active period. Through contextualizing epistolary material—such as letters in manuscript and print form, letter collections, and epistolary manuals, as well as sources in other genres that describe letter writing practices—I explore the multifaceted uses of letter writing for literati officials. The study provides a systematic view of the functions of Song letter writing in political, social, and cultural realms by investigating its complex practices. Using letters in several sub-genres by important literati figures such as Mi Fu, Li Gang, and Sun Di, it illustrates the main aspects of letter writing, including format, rhetoric, topical content, and handwriting. In view of the roles played by letters exchanged among Song scholars, this research on literati correspondence provides a window on how interpersonal relationships were conducted by written exchanges during that period. It also sheds light on how epistolary culture was transformed by the literati community during one of the key periods of Chinese civilization. These insights will contribute to the research of Chinese literati culture and related fields, such as the social history of middle period China, and will also be useful for comparing China’s epistolary culture with the world’s other letter writing traditions.